The impact of social media marketing on instagram for cosmetic brands in Indonesia - Tedi Rustandi; Faizatun Faizatun; Derriawan Derriawan (Enrichment : Journal of Management, 2023)
Opportunities and challenges in several aspects of Indonesia, such as the number of cosmetic companies by 78.34% (2021), the increase in the GDP of the cosmetics sector by 9.61% (2021), the increase in registered cosmetic products by 53.65% (2022), and the low level of purchase return of cosmetic products increased competition between cosmetic brands in Indonesia. This study analyzes the impact of social media marketing for the Wardah, Revlon, and Pixy brands on Instagram on brand image, brand awareness, purchase decision, and repurchase intention. Data was collected through a survey using the convenience technique of 175 respondents who were followers of the Wardah, Revlon, and Pixy brands. Data analysis used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Social media marketing research results affect brand awareness and brand image and do not affect purchase decision and repurchase intention. Brand awareness affects brand image, purchase decision, and repurchase intention. Brand image does not influence purchase decision and repurchase intention. Purchase decisions affect repurchase intentions.This research provides insight into the application of social media marketing in Indonesia on the Instagram platform, which has a complex relationship with brand awareness, brand image, purchase decision, and repurchase intention